Aplikasi Pembayaran Uang Kuliah Pada Universitas Prima Indonesia Menggunakan Metode Fuzzy Logic Berbasis Android - Aurelia Xinara Lim; Fransisca; Jepri Banjarnahor (Jurnal Sains dan Teknologi, 2020)
< >Payment of tuition fees is an obligation for every student to acquire knowledge in college. At the University of IndonesiaIndonesia, the payment of tuition fees is still using a manual system where every student who comes is notified of the amount oftuition fees to be paid orally or in writing, as in the Universitas Prima Indonesia system. This has several drawbacks where the longpayment process is caused by a long queue system, or the number of students arriving at one time. The application uses fuzzy logicmethods in transactions so that the system can separate transactions that have been paid and transactions that have not been paid.Author-designed apps can help speed up entering transactions. The application designed by the author uses smartphone technologybased on Android to assist transactions so that it is easy to carry anywhere